Dynamic Tribological Behavior of a Cone Bit Helical Composite Seal - Zhou, Yi; Zhou, Yi; Wang, Zicong; Jiang, Yang (Scientific Journal of Technology, 2026)
This study investigated the tribological behavior of helical composite seals for high-speed cone bits under dynamic loading through an integrated experimental–computational approach, systematically elucidating their wear mechanisms. To address limitations of the classical Archard model’s static assumptions, an innovative framework for predicting dynamic wear was developed by coupling time-varying contact stress integration with Hertzian contact theory, establishing explicit dynamic correlations among load–geometry wear parameters to enable real-time wear volume prediction. Wear evolution was comprehensively analyzed using a UMT TriboLab tribometer coupled with a three-dimensional white light interferometer for characterizing topography. Cyclic loading spectra were used to quantify wear progression in ball-on-block point contacts with peak loads from 20 to 50 N at frequencies from 1/24 to 1/12 Hz. Experimental results demonstrated an exponential relationship between peak load and wear volume (R²=0.98), with frequency doubling significantly exacerbating fatigue damage (50.1% greater wear volume at 1/12 Hz than at 1/24 Hz). Stress concentration at helical seal tooth roots formed maximum contact pressure zones, inducing radial propagation of partial-wear cracks. Notably, sealing interfaces maintained effective hydrodynamic barriers even under extreme conditions (400 N or 4 Hz operation). The key findings were verified through synchronous monitoring of the pressure distribution of the interfacial film and transient leakage rates. This study has advanced wear analysis and provided a highly precise theoretical basis for optimizing multiple factors and predicting the service life of the sealing system of deep-drilling equipment.